The Use of Mathematical Intelligence Stick Media to Stimulate Number Recognition Skills in Children Aged 5-6 Years - Sari, Ani Sartika; Kasmiati; Utami, Winda Sherly (UNIB Press, 2025)
Mastery of number concepts is a crucial foundation for cognitive development in early childhood, but is often hindered by learning methods that are often abstract and monotonous. This study aims to analyze the effectiveness of the Mathematical Intelligence Stick media in improving number symbol recognition skills in 5-6 year old children at Harapan Bunda Kindergarten. This study applied a quantitative approach with a Pre-Experimental One Group Pretest-Posttest design, involving 15 children selected through saturated sampling techniques. The findings showed a substantial improvement, with the average score of children's abilities increasing sharply from 12.73 in the pretest to 20.46 in the posttest. Effect size analysis using Cohen's d yielded a value of 2.64, indicating a powerful effect. This indicates that the integration of manipulative sticks successfully bridges children's understanding from the enactive to the symbolic level, while stimulating fine motor skills. This study concludes that the Mathematical Intelligence Stick is an effective pedagogical tool for fostering concrete, interactive, and meaningful mathematics learning in early childhood